2022
DOI: 10.3390/cells11121865
|View full text |Cite
|
Sign up to set email alerts
|

Myh9 Plays an Essential Role in the Survival and Maintenance of Hematopoietic Stem/Progenitor Cells

Abstract: Myosin heavy chain 9 (MYH9) gene encodes a protein named non-muscle heavy chain IIA (NMHC IIA), interacting with actin and participating in various biological processes. Mutations in MYH9 cause an array of autosomal dominant disorders, known as MYH9-related diseases (MYH9-RD). However, the role of MYH9 in normal hematopoiesis remains largely unexplored. By using Mx1-cre Myh9 conditional knockout mice, we established an inducible system to precisely inactivate Myh9 function in hematopoietic cells in vivo. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Myosin heavy chain 9 (MYH9), part of the myosin family, participates in cell adhesion, polarity, motility and migration [4]. MYH9 is a skeletal protein and plays a critical role in multiple human diseases [5][6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Myosin heavy chain 9 (MYH9), part of the myosin family, participates in cell adhesion, polarity, motility and migration [4]. MYH9 is a skeletal protein and plays a critical role in multiple human diseases [5][6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…Myosin heavy chain 9 (MYH9), part of the myosin family, participates in cell adhesion, polarity, motility and migration [4]. MYH9 is a skeletal protein and plays a critical role in many human diseases [5][6][7][8][9]. Over the past several years, more and more studies have shown that MYH9 is increased in many cancers, such as non-small cell lung cancer [10], colorectal cancer [11], prostate cancer [12], diffuse large B-cell lymphoma [13], renal cell carcinoma [14], glioma [15] and hepatocellular carcinoma [16].…”
Section: Introductionmentioning
confidence: 99%
“…5G), which revealed an association between quercetin and the MYH9 protein. The MYH9 protein, a fundamental constituent of the cellular skeleton, plays a critical role in preserving and facilitating the functionality of HSCs [37]. Additionally, it exerts in uence over immune cells and regulates the cytotoxicity of NK cells [38].…”
Section: Quercetin Targets the Myh9 Proteinmentioning
confidence: 99%
“…MYH9 was detected as binding to GSN in a high throughput screen (51). It is needed for survival of HSPC (52), regulates mature B-cell functions (53) and has an important contribution in hematologic malignancies (54)(55)(56).…”
Section: Genes Needed For Overall Fitnessmentioning
confidence: 99%